THE USE OF PROJECT-BASED LEARNING IN DEVELOPING SOCIAL AND COMMUNICATION SKILLS OF PRIMARY SCHOOL LEARNERS (World Bulletin of Education and Learning, 2025)
The development of social and communication skills is a central objective of primary education, as these competencies form the basis for successful interaction, cooperation, and personal development of learners. In contemporary educational practice, increasing attention is given to teaching approaches that actively involve pupils in meaningful learning experiences and promote interaction among learners. This article examines the use of project-based learning as an effective pedagogical approach for developing social and communication skills of primary school learners. Project-based learning is understood as a learner-centered methodology that engages pupils in collaborative tasks aimed at solving real-life or meaningful problems over an extended period of time. The study highlights the pedagogical potential of project-based learning in creating interactive learning environments where pupils practice communication, teamwork, responsibility, and mutual respect. Particular attention is given to the alignment of project-based learning with the psychological and developmental characteristics of primary school learners. The article argues that systematic implementation of project-based learning contributes to the formation of essential social behaviors and communication abilities by encouraging cooperation, dialogue, and reflective interaction. The findings emphasize the importance of teacher guidance, careful project design, and supportive classroom conditions in ensuring the effectiveness of project-based learning in primary education.
Keywords: project-based learning, social skills, communication skills, primary education, collaborative learning